Training on Packaging and Marketing Produk for MSMEs in Kasemen - Galih Ginanjar Saputra; Solehatin Ika Putri; Muhammad Johan Widikusyanto (MOVE: Journal of Community Service and Engagement, 2021)
The problem of marketing product is the biggest obstacle for a number of MSMEs. This is due to the lack of public knowledge about the marketing process and important activities before marketing, one of which is product packaging. Implementation is carried out through training and practice regarding product packaging and marketing. The results of the activity are partners are able to understand the importance of product packaging and labeling/branding and know how to make product packaging so that the product is more attractive and has an identity. In addition, partners are also able to understand the importance of product marketing and know how to market products effectively to increase sales and increase income.